The Importance of Controlling the Preparation of Budgetary Management Documents for Public Investment Expenditures in Rationalizing State Spending within the Framework of the New Budgetary Reform of 2023 – A Field Study at the Directorate of Programming a - ammari, takieddine; belgueliel, noureddine (Journal of Research in Finance and Accounting, 2025)
Through this study, we attempted to identify the importance of controlling the preparation of budgetary management documents for public investment expenditures in rationalizing state spending, in light of the new budgetary reform introduced starting from 2023. To achieve the objectives of the study, we processed and analyzed the opinions of 43 employees working in the Directorate of Programming and Budget Follow-up and the Budgetary Control Authority in M’sila Province, given that these two institutions play a role in accompanying and monitoring the preparation of the new budgetary management documents introduced by the reforms. Data were collected through a questionnaire designed as a tool to analyze the responses of the sample members, and the necessary statistical methods were employed to test the hypotheses. The study concluded that there is a positive causal relationship between controlling the preparation of budgetary management documents for public investment expenditures (independent variables) and the rationalization of state spending (dependent variable), which means that such control effectively contributes to rationalizing state expenditures.